Perkawinan Poligami: Studi Komparatif Hukum Islam dan Hukum Perdata Dalam Pembagian Harta Waris - Aditia Urbaningrum; Adhimaz Kondang Pribadi (Faculty of Law Universitas Muhammadiyah Metro, 2025)
Polygamous marriage is the marriage of a man with more than one woman at the same time. In polygamous marriages, inheritance disputes become a problem that often occurs. This is due to injustice in the distribution of inheritance and lack of understanding and knowledge of the law. The division of inheritance in polygamous marriages under Islamic law is based on the Compilation of Islamic Law Article 94 as well as in Surah An-Nisaa verse 12. While in the division of polygamous marriage inheritance in civil law is based on article 852a of the Civil Code, where in the division of heirs if the marriage is the second or subsequent marriage, and from the marriage that used to have a child or offspring of the child, the husband / wife must not inherit more than the distmayed part received by one of the children and the husband / wife part should not be more than 1/4 of the heir's inheritance.